Peningkatan Kemampuan Berhitung Melalui Media Magic Box - Desrianis; Ismet, Syahrul (UNIVERSITAS SERAMBI MEKKAH, 2025)
The background of the research is that children's ability to count is not yet optimal, saying the order of numbers 1-10, matching number symbols with the number of objects and knowing the concept of many and few. The research aims to improve the counting skills of young children through magic box media. The research was a classroom action carried out at the pos Paud Mentari kota Sawahlunto with a total of 8 children, consisting of 5 girls and 3 boys who were the subjects of this research. The methodology used in this classroom action research is descriptive qualitative methodology. The research uses the Kemmis Taggar cycle model which has 2 cycles, namely cycle I and cycle II, where each cycle consists of 4 stages, namely planning, implementation, observation and reflection. Research data was collected in three ways, observation and documentation. The data analysis technique uses percentages in each lesson. Based on the actions taken, the highest score of 82.5% was achieved in children's ability to count using magic box media. From the initial conditions it can be seen that the criteria for developing very well was 12.5%, and increased to 82.5% in cycle II for the criteria